(untitled) (Global Journal of Human-Social Science, 2020)
How to achieve happiness is a constant concern in ancient philosophy and also in Christian thought All schools and their most representative thinkers in one way or another have referred to what behavior must be followed to escape the designs of fate if it exists and not fall into the wrong personal decisions and to get happiness Thus this concern is analyzed and synthesized here based on virtue as the central axis In addition certain contributions of contemporary philosophy about it are taken into account knowing that Ethics centered on the individual is a reality that always adds concepts of great importance